ANALYSIS OF CEMENTING WELLS X-1 and Y-1 USING MULTIFUNCTION ULTRASONIC IMAGING LOGGING TOOL - Henk Subekti; Purnomosidi Purnomosidi; Edi Untoro; Arya Dwi Candra; Mefriadi Mefriadi (Journal of Petroleum and Geothermal Technology, 2023)
By analyzing the measurement principle of the ultrasonic pulse method, a multifunctional ultrasonic image recording device and the application of the measurement technique were designed. It can perform surface imaging well in high-resolution imaging mode in open holes. Can also perform casing inspection and cement bond evaluation in full wave mode at casing holes. The proposed tool was tested in practice. This shows that this tool can evaluate geological feature information such as fractures and layered structures in open holes. Imaging casing thickness, inner and outer diameters and cement impedance can also be measured at casing holes. Cement analysis in wells Logging Tool (MUIL), cement slurry design and operations during cementing. The logging results above can be analyzed quantitatively including amplitude readings which can then determine compressive strength prices and bond index prices. Meanwhile, qualitative analysis was carried out comprehensively from VDL recordings and using the Enhanced Logging Imaging System. For analysis from a design perspective, it looks at the cement slurry planning, while from an operational perspective it looks at the suitability between planning and implementation in the field.